2001
DOI: 10.1073/pnas.241494198
|View full text |Cite
|
Sign up to set email alerts
|

Pulse confinement in optical fibers with random dispersion

Abstract: Short-range correlated uniform noise in the dispersion coefficient, inherent in many types of optical fibers, broadens and eventually destroys all initially ultra-short pulses. However, under the constraint that the integral of the random component of the dispersion coefficient is set to zero (pinned), periodically or quasiperiodically along the fiber, the dynamics of the pulse propagation changes dramatically. For the case that randomness is present in addition to constant positive dispersion, the pinning res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 23 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…It is shown that adding quenched disorder to the equidistant natural frequencies (3.38), the system loses its ability to achieve pulses. A similar effect in optical fibers is the pulse degradation through small random contributions to the chromatic dispersion along the fiber [83]. The systematic variation of the natural frequencies (3.49) with dependance on the mode index was conceived in order to emulate the effects of dispersion, which turned out to have only a small effect on the pulse shape for mode-locked phase oscillators.…”
Section: A Qualitative Comparison Of the Mode-locking Phenomenamentioning
confidence: 99%
“…It is shown that adding quenched disorder to the equidistant natural frequencies (3.38), the system loses its ability to achieve pulses. A similar effect in optical fibers is the pulse degradation through small random contributions to the chromatic dispersion along the fiber [83]. The systematic variation of the natural frequencies (3.49) with dependance on the mode index was conceived in order to emulate the effects of dispersion, which turned out to have only a small effect on the pulse shape for mode-locked phase oscillators.…”
Section: A Qualitative Comparison Of the Mode-locking Phenomenamentioning
confidence: 99%
“…The effect of a random variation of GVD on MI has been studied extensively [25][26][27][28][29] for the particular case where the GVD is perturbed by a Gaussian white noise, which is explicitly solvable. Under these conditions a deformation of the conventional MI gain profile due to the random perturbation was found when the unperturbed fiber has an anomalous dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the theoretical modeling considered ideal fibers with fixed core diameter and doping concentration. In reality, real fibers often include various imperfections due to fluctuations of the cross-section area, dopant concentration, inhomogeneities of the refractive index, bending, ellipticity and external stress, etc [44,45]. These imperfections may be random, manifesting themselves through random effective GVD.…”
Section: Introductionmentioning
confidence: 99%